Editor's Note - Russel J. Reiter (Journal of Current Science and Technology, 2013)
Knowledge is meant to be shared. To advance science and improve human health and wellbeing, when new information is uncovered by scientists (here used in the broadest sense), it is their obligation to make it available to anyone who is interested. Knowledge that is not disseminated is knowledge wasted on but a few individuals. The dispersal of newly discovered data is both an obligation and a goal of a scientist/educator. This is most frequently done by publishing previously unknown information in refereed biomedical journals. The cloistering of data in the minds of only the discoverers of the information defeats the purpose of scientific inquiry. Publishing new information in scientific journals has been described as the best educational system ever devised. When this is done, especially in today’s technically-savvy society, the information is immediately accessible to millions of individuals worldwide. Moreover, unless the data is accidently or intentionally destroyed, it remains available far into the indefinite future. This is the mission and the rationale for scientists/educators to communicate by means of their publications.